The follow up of complex infants in an aerodigestive clinic. (December 2022) - Kaspy, Kimberley R.; Burg, Gregory; Garrison, Aaron P.; Miller, Claire K.; Pentiuk, Scott; Smith, Matthew M.; Benscoter, Dan
Highlights: Appreciate the role of an aerodigestive program in the management and follow up of complex infants. Understand the benefits of aerodigestive care for infants with complex medical and surgical conditions. Recognize the presence of aerodigestive conditions in the neonatal intensive care unit. Consider the applicable practice model to provide aerodigestive care in their institution. Abstract: The current available literature evaluating pediatric multidisciplinary aerodigestive programs for the management of aerodigestive disorders in infants was reviewed. Multidisciplinary aerodigestive programs have emerged to provide coordinated and comprehensive care for the growing population of children with aerodigestive conditions, including complex airway, pulmonary, gastrointestinal, and feeding disorders, which are prevalent among infants discharged from the neonatal intensive care unit (NICU). The team approach central to aerodigestive clinics offers a comprehensive diagnostic workup and unified management plan through consolidated interdisciplinary clinics, combined endoscopic procedures, and regular team discussions, leading to improved resource utilization and health care outcomes. We review common conditions presenting in the NICU that benefit from the aerodigestive model of care, including esophageal atresia, prematurity, bronchopulmonary dysplasia with or without tracheostomy or ventilator dependence, and dysphagia.